Philosophical Texts: Character Education for Minangkabau Women - Hamdan Hasibuan; Muhammad Roihan Daulay; Mowafg Masuwd (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
This study focuses on the concept of ideal women according to Minangkabau philosophy. The criteria of the ideal women can be found in proverbs containing implicit meaning related to ethical values, namely the view about women's ideal morality. The interpretation can be comprehended from its function and purposes as a concept of moral and character education for the Minangkabau young generation. The study toward the character education for Minangkabau women is based on the interpretation meaning from the concept of Minangkabau ideal women became the basis fine art creative idea resulting in the icon of personal expression. This artwork was materialized into the painting symbolic expression/abstraction by borrowing the traditional idiom